AHLUSSUNAH WAL JAMAAH'S POLITICAL PRACTICES IN POST-REFORM INDONESIA - Ahmad Zubaidi (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
Islamic politics in Indonesia is very distinctive and has characteristics as a reflection of Indonesian Muslims who understand ahlussunnah wal jamaah so that the aspect of compromise and promoting togetherness, and attaching importance to stability is undeniable. However, that was before, later after the reformation, when the faucet of freedom was opened in Indonesia, many political ideologies entered Indonesia. They tried to change the established Indonesian political order, such as the emergence of the sharia formalization movement, the desire to establish an Islamic state, and the Islamic caliphate. The political activity of this model is increasingly visible in the era of President Jokowidodo as a symbol of resistance. This paper tries to elaborate and analyze with a descriptive analysis system on the phenomena in post-reform Indonesia. It is interesting because there are symptoms that the political doctrine of Aswaja will be defeated by the momentary political doctrines and the doctrines of khilafahism. However, during this upheaval, Aswaja's power and doctrine proved to endure despite the worrying erosion. Politik Islam di Indonesia sangat khas dan berkarakteristik sebagai cerminan umat Islam Indonesia yang berpaham ahlussunnah wal jamaah, sehingga aspek kompromi dan mengedepankan kebersamaan dan mementingkan stabilitas angat kentara. Tapi itu dulu, belakangan pasca refeormasi, ketika kran kebebasan dibuka di Indonesia, banyal ideology politik masuk ke Indonesia dan berusaha merubah tatanan politik indonnesia yang sudah mapan, seperti munculnya gerakan formalisasi syariah, keinginan mendirikan Negara Islam, dan khiafah islamiyah. Bahkan aktifitas politik model ini semakin kentara di ere Presiden Jokowidodo sebagai symbol perlawanan. Tulisan ini mencoba mengelabirasi dan menganalisis dengan system analisis deskriptif terhadap fenomena yang terjadi di Indonesia pasca reformasi. Hal ini menarik karena ada gejala doktrin politik aswaja akan terkalahkan oleh doktrin politik sesaat dan doktin-doktin khilafihisme. Namun, di tengah pergolakan ini, kekuatan aswaja dan doktrinnya terbukti dapat bertahan walau di tengah erosi yang mengkhawatirkan.